2008
DOI: 10.1021/jm800456k
|View full text |Cite
|
Sign up to set email alerts
|

Adamantyl-Substituted Retinoid-Derived Molecules That Interact with the Orphan Nuclear Receptor Small Heterodimer Partner: Effects of Replacing the 1-Adamantyl or Hydroxyl Group on Inhibition of Cancer Cell Growth, Induction of Cancer Cell Apoptosis, and Inhibition of Src Homology 2 Domain-Containing Protein Tyrosine Phosphatase-2 Activity

Abstract: (E)-4-[3-(1-Adamantyl)-4′-hydroxyphenyl]-3-chlorocinnamic acid (3-Cl-AHPC) induces the cell-cycle arrest and apoptosis of leukemia and cancer cells. Studies demonstrated that 3-Cl-AHPC bound to the atypical orphan nuclear receptor small heterodimer partner (SHP). Although missing a DNA-binding domain, SHP heterodimerizes with the ligand-binding domains of other nuclear receptors to repress their abilities to induce or inhibit gene expression. 3-Cl-AHPC analogues having the 1-adamantyl and phenolic hydroxyl pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 57 publications
0
38
0
Order By: Relevance
“…In the case of DAX-1 and SHP, there has been much speculation but little progress, perhaps with the notable exception of adamantyl-substituted retinoids binding to SHP [56]. Docking of the compounds CD437/AHPN and MM002/AHPC to a SHP structure model suggested how these compounds could influence SHP activity as true pocket ligands [57]. A potential problem with this method could be that the SHP in silico structural model in this study is based on the X-ray structure of liganded ultraspiracle (USP), which is the Drosophila RXR homologue and only distantly homologues to the SHP LBD.…”
Section: No Pockets-no Ligands?mentioning
confidence: 99%
“…In the case of DAX-1 and SHP, there has been much speculation but little progress, perhaps with the notable exception of adamantyl-substituted retinoids binding to SHP [56]. Docking of the compounds CD437/AHPN and MM002/AHPC to a SHP structure model suggested how these compounds could influence SHP activity as true pocket ligands [57]. A potential problem with this method could be that the SHP in silico structural model in this study is based on the X-ray structure of liganded ultraspiracle (USP), which is the Drosophila RXR homologue and only distantly homologues to the SHP LBD.…”
Section: No Pockets-no Ligands?mentioning
confidence: 99%
“…Substitution of the adamantyl group with a phenyl group in this class of compounds resulted in a 250-fold loss in activity against an ovarian cancer cell line [107]. The ortho disposition of the bulky adamantyl group to the phenolic OH group was also found to be important in activity, in addition to the distance between the adamantyl group and the carboxylic acid [107,110]. Molecular docking experiments between an analogue of 23 and the retinoic acid receptor-g showed an interaction between the adamantyl group and isoleucine and leucine residues [108].…”
Section: Anticancer Agentsmentioning
confidence: 95%
“…Very interestingly, this seems to be not an artifact of the crystallization procedure since the same allosteric binding site has been found as functional in other nuclear receptors such as the steroidogenic factor-1 (SF-1) and LHR-1 [42, 43]. In previous works, we already used the 1G2N structure of USP as template to model the structural features of SHP and its interaction with compounds 1 and 2 [22, 32]. …”
Section: Resultsmentioning
confidence: 93%
“…Thus, the combination of these studies gives rise to an intriguing scenario where small molecules oppositely regulate SHP functions. In line with these observations, further studies by Dawson and coworkers reported the importance of the carboxylic moiety of 1 and 2 for the apoptotic activity and, more recently, an interaction model of these compounds at the proposed ligand binding site of SHP has been suggested, though pending for further experimental appraisals [31, 32]. …”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation